Therapeutic Dilemma of Sarcoidosis and Treatment-naïve Hepatitis C Manifesting as Tattoo Reactions - Ishimaru, Naoto (Intern Med, 2020)
A 23-year-old man had an 8-day history of fatigue and dry cough and papulo-nodular reactions on his extensive tattoos. Chest radiography revealed several small granular shadows, and a transbronchial lung biopsy showed non-caseating epithelioid cell granuloma. A skin biopsy of the tattooed area showed histiocytic infiltrates with phagocytized tattoo pigment. Antibody tests for hepatitis C virus were positive. The patient was successfully treated with corticosteroid therapy, and after inflammation was suppressed, he received delayed anti-viral therapy. Sarcoidosis should be considered as a concurrent condition if papules are presented on the tattoos of patients with hepatitis C.